UNITARY STATE IN KOSOVO: CONSTITUTIONAL CHALLENGE AND RISK OF FRAGMENTATION BY THE ASSOCIATION OF SERB-MAJORITY MUNICIPALITIES (Lex localis - Journal of Local Self-Government, 2025)
This article analyses the concept of the unitary state in the European context, with a particular focus on the case of Kosovo under the 2008 Constitution. Initially, the unitary model is treated as a governance structure that guarantees territorial integrity and institutional clarity, drawing on examples from France and the United Kingdom. The article explores how Kosovo has adopted this model, balancing it with an advanced level of decentralization to address ethnic diversity and political challenges.In the second part, the implications of the creation of the Association of Serb-Majority Municipalities, are discussed and how this proposed structure threatens the unitary character of the Kosovo state. Analyzing comparative examples from Bosnia and Herzegovina, Belgium, Italy, Croatia and Spain, the article highlights the risks of autonomous structures that can lead to institutional fragmentation and political polarization. The article concludes by emphasizing that a cautious approach to decentralization, supported by the rule of law and a commitment to state integrity, is needed to preserve the unitary state of Kosovo.The methodology used in this article is based on the normative-constitutional analysis of the provisions of the Constitution of Kosovo and relevant legal acts, combined with a comparative approach through the study of models of unitary states in Europe. The article builds the argumentation through the analysis of the content of constitutional and legal documents, as well as through the critical interpretation of relevant jurisprudence and doctrine, in order to assess the risk that the Association of Serb-Majority Municipalities may pose to the unitary character of the state of Kosovo.